Psychological Empowerment and Job Satisfaction in the Banking Sector - George, Elizabeth (Springer International Publishing, 2018)
This book explores how psychological empowerment can influence and enhance job satisfaction. The authors argue that in today's working climate the wellbeing and involvement of employees is of utmost importance to any company's overall success and that management techniques like empowerment are the most effective means of achieving this goal. Based on an empirical study examining job satisfaction amongst employees of several private sector, public sector and new generation banks in Kerala, India as well as extensive literature review, this book discusses the role psychological empowerment plays in enhancing job satisfaction both locally and internationally. It goes on to analyze four dimensions of psychological empowerment and the role of job satisfaction in the relationship between psychological empowerment and job related stress. This book will be of great interest to scholars in management and psychology and is essential reading for industrialists and managers wanting to apply empowerment strategies in their own workplace.